2004
DOI: 10.2337/diacare.27.suppl_2.b10
|View full text |Cite
|
Sign up to set email alerts
|

Who Has Diabetes? Best Estimates of Diabetes Prevalence in the Department of Veterans Affairs Based on Computerized Patient Data

Abstract: OBJECTIVE -To optimize methods for identifying patients with diabetes based on computerized records and to obtain best estimates of diabetes prevalence in Department of Veterans Affairs (VA) patients.RESEARCH DESIGN AND METHODS -The VA Diabetes Epidemiology Cohort (DEpiC) is a linked national database of all VA patients since 1998 with data from VA medical visits, Medicare claims, pharmacy and laboratory records, and patient surveys. Using DEpiC, we examined concordance of diabetes indicators, including ICD-9-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
332
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 379 publications
(342 citation statements)
references
References 32 publications
9
332
0
Order By: Relevance
“…45 In a study using the VA database, the sensitivity and specificity of ICD-9 codes in comparison to chart review to identify diabetes were 78.3 and 95.7 %, respectively. 46 The use of ICD-9 codes in general and AHRQ-CCS codes in particular in order to extract obesity diagnoses has been described in the literature [47][48][49][50] ; AHRQ-CCS codes for obesity have also been used to generate reports on utilization and cost statistics in relation to obesity. [51][52][53] In general, the use of ICD-9 codes to identify obesity has been noted as having low sensitivity but high specificity 45,54 ; using chart review as the gold standard, the sensitivity, specificity, positive predictive value, and negative predictive value were 24.6 %, 99.3 %, 75.9 %, and 93.6 %.…”
Section: Discussionmentioning
confidence: 99%
“…45 In a study using the VA database, the sensitivity and specificity of ICD-9 codes in comparison to chart review to identify diabetes were 78.3 and 95.7 %, respectively. 46 The use of ICD-9 codes in general and AHRQ-CCS codes in particular in order to extract obesity diagnoses has been described in the literature [47][48][49][50] ; AHRQ-CCS codes for obesity have also been used to generate reports on utilization and cost statistics in relation to obesity. [51][52][53] In general, the use of ICD-9 codes to identify obesity has been noted as having low sensitivity but high specificity 45,54 ; using chart review as the gold standard, the sensitivity, specificity, positive predictive value, and negative predictive value were 24.6 %, 99.3 %, 75.9 %, and 93.6 %.…”
Section: Discussionmentioning
confidence: 99%
“…The final study cohort included individuals with concurrent diagnoses of Type 2 diabetes, identified as those who had at least 2 inpatient or outpatient records with diagnostic codes of 250.x0 or 295.x2, 357.2, 362.0, or 366.41 (Miller et al, 2004) during the study period. In order to increase the precision of case identification for Type 2 diabetes, we excluded 1129 persons who either only had records with diagnostic codes of 250.x1 or 250.x3 (who may have had Type 1 diabetes) or who only had one or more prescriptions for hypoglycemic medications.…”
Section: Study Samplementioning
confidence: 99%
“…We also present information on multimorbidity grouped by mental versus physical disorders. 20 The NPCD is the source for the VHA Medical SAS data sets used to analyze veteran clinical data such as diagnosis and procedure codes for outpatient visits and inpatient admissions. The PBM database includes utilization information for every prescription filled in the VA, with the Outpatient Pharmacy Package for individual prescriptions dispensed at the site's pharmacy, either as a new fill or a refill.…”
Section: Introductionmentioning
confidence: 99%